(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines specific aspects of the figurative type of speech in connection with the relationship between language and speech, the status of language as a social phenomenon, its potential as an abstract entity and the manifestation of this potential in speech. Modality and its types are studied, the expression of modality in the image is revealed. It is based on the nonspecificity of the substance expressed by verbal moods in figurative speech. The means of expressing modal meaning in the visual type of speech are identified and their place in the speech structure is indicated.